Teater Tradisional sebagai Dokumen Komunitas - Ninuk Kleden-Probonegoro (Antropologi Indonesia, 2000)
The assumption that theater functions as a document of the community falls under question. Such an assumption emerges, for example, from the ideas of Paul Ricoeur on theories of the text, which takes textual discourse as an inscription of oral discourse. Social reality is seen as oral discourse, allowing for the view that the narrative aspect of theater presents its textual discourse. The classic study of the ludruk theater by James Peacock demonstrates haw the ludruk holds within it the anxieties of members of the ludruk community in East Java over modernization. In Ricoeur's terms, such anxieties are inscribed in ludruk performances. Holding to the assumption of theater as document, one would expect to see performances related to the reformation movement of the present. However, the 'Gaya Baru' Lenong Theater, performed by the 'Sarkim' group at a wedding occasion on March 20, 1999 in the village of Jelabong, East Buaran, Serpong, displays no significant inclinations toward the reformation. During the performance that ran until 3.45 in the early morning, the author recorded only three pertinent words from the panjak's jokes: krisis, sembako and PHK. This leads to following question: should the assumption of the role of traditional theater in documenting the community be revised; or does the community see no importance in there formation that is occurring at the national level?